Variations in Concentration and Carbon Isotope Composition of Methanotroph Biomarkers in Sedge Peatlands Along the Altitude Gradient in the Changbai Mountain, China - Zhao, Meiling; Wang, Ming; Zhao, Yantong; Jiang, Ming; Wang, Guodong (Frontiers in Microbiology, 2022)
Northern peatlands are one of the largest natural sources of atmospheric methane globally. As the only biological sink of methane, different groups of methanotrophs use different carbon sources. However, the variations in microbial biomass and metabolism of different methanotrophic groups in peatlands along the altitude gradient are uncertain. We measured the concentrations and metabolic characteristics of type Ⅰ (16:1ω7c, 16:1ω5c) and type Ⅱ (18:1ω7c) methanotroph biomarkers using biomarkers and stable isotopes in eight Carex peatlands along an altitude gradient from 300 m to 1500 m in the Changbai Mountain, China. We found that the trends with altitude in concentrations of the type Ⅰ and type Ⅱ methanotroph biomarkers were different. The dominating microbial group changed from type Ⅰ methanotroph to type Ⅱ methanotroph with increasing altitude. The concentrations of type I and type II methanotroph biomarkers were significantly affected by the total phosphorus and total nitrogen, and the dissolved organic carbon, respectively. The δ13C values of type Ⅰ methanotroph biomarkers changed significantly along the altitude gradient, and they were more depleted than type Ⅱ methanotroph biomarkers, which indicates the difference in carbon source preference between type I and type II methanotrophs. This study highlights the difference of the concentration and carbon source utilization of type I and type Ⅱ methanotrophic groups along the altitude gradient, and enhances our understanding of the metabolic process of methane mediated by methanotrophs and its impact on carbon-sink function in northern peatlands.